Effect of 3-(1H-Pyrrol-2-yl)-1H-Indazole on the Antioxidant Status of Rats - Karatas, Fikret; Coteli, Ebru; Aydin, Suleyman; Servi, Suleyman; Kara, Haki (Humana Press Inc, 2010)
The influence of injection periods of 3-(1H-pyrrol-2-yl)-1H-indazole regarding vitamins A, E, C, selenium (Se), malondialdehyde (MDA) levels, and glutathione peroxidase (GSH-Px) activity in rats has been investigated. The substance was given by subcutaneous injection at 20 mg/kg every other day for a total of 15 injections. At the end of the treatment, Se levels in serum were determined by fluorimetry, and those of vitamins A, E, C, and malondialdehyde in serum, liver, and kidney were determined by high-performance liquid chromatography. GSH-Px activities in erythrocytes were determined spectrophotometrically. Vitamins A, E, C, and Se levels were generally lower than in the controls, while GSH-Px activity at the third injection period was maximally increased, with the activities after the other injection periods being higher than in the control group. In addition, vitamins A, E, and C levels were generally lower than the control groups, while serum, liver, and kidney MDA levels gradually increased depending on injection periods. On the other hand, GSH-Px activity was higher than in the control group. Thus, the results show that while vitamins A, E, C, and Se levels decreased, MDA levels and GSH-Px activities increased after administration of 3-(1H-pyrrol-2-yl)-1H-indazole to the rats. These findings might be related to the increased amount of free radicals caused by 3-(1H-pyrrol-2-yl)-1H-indazole injection.
Keywords: Indazole; Vitamins (A, E and C); Se; MDA; GSH-Px; Rat